Biomechanical assessment of vulnerable plaque: from histological evidence to ultrasound elastography and image-based computational patient-specific modelling - Curcio, Nicoletta; Conti, Michele; Cardani, Rosanna; Renna, Laura Valentina; Dell’Antonio, Giacomo; Bari, Vlasta; Nano, Giovanni; Matrone, Giulia; Mazzaccaro, Daniela (Frontiers in Bioengineering and Biotechnology, 2025)
The assessment of carotid plaque vulnerability is a relevant clinical information that can help prevent adverse cerebrovascular events. To this aim, in this work we study the ability of different non-invasive methods for assessing plaque vulnerability in patients undergoing carotid endarterectomy (CEA). Histological examinations of patients’ plaque samples were conducted after CEA while ultrasound (US) and computed tomography angiography (CTA) acquisitions were performed preoperatively. US acquisition included point shear wave elastography (p-SWE) and a radio frequency echo-based wall tracking mode for the evaluation of arterial wall stiffness. CTA images were segmented, and the results were used for an ad hoc procedure that semi-automatically reconstructed the atherosclerotic wall providing a 3D model of the different plaque components to perform patient-specific finite element analysis (FEA) of stress distributions. One hundred patients were involved in the study and a macroscopic assessment of the surgeon was used to classify carotid atherosclerotic plaques as vulnerable or stable. The data derived from histological analysis, US acquisitions and FEA were correlated with the outcome of the classification. Indeed, histological features differentiated between vulnerable and stable plaques, confirming the surgeon’s classification. From p-SWE, the measurement of Young’s Modulus (YM) in stable plaques was significantly higher than in vulnerable plaques. Also stress indexes related to the Von Mises and Max Principal stresses from FEAs showed statistically significant differences between plaque groups. These results demonstrate that both stiffness-related US measurements and stress parameters derived preoperatively from computational analyses were able to differentiate patients with vulnerable plaques from ones with stable plaques. Thus, the development and application of new methods for a non-invasive biomechanical assessment of atherosclerotic artery walls could give valuable information for plaque vulnerability evaluation.